Manajemen Aset dan Nilai Perusahaan Manufaktur yang Terdaftar di BEI - Teguh Erawati; Febronia Fayulan Wuleng (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to prove the effect of asset management and dividend policy on firm value. The sampling technique used purposive sampling method. The population in this study is 193 companies which are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019 with a total sample of 54 companies that meet the criteria. The method of analysis using SPSS statistical applications. The independent variables in this study are asset management and dividend policy. The dependent variable in this study is firm value which is calculated by the Tobin's Q method. The results of this study indicate that asset management has a positive effect on firm value. Dividend policy has a negative effect on firm value. Keywords: asset management, dividend policy and firm value